Astaxanthin Nanoemulsion Formulation and Evaluation - Yanni Dhiani Mardhiani; Deny Puriyani A; Lailatul Fadilah (Indonesian Journal of Pharmaceutics, 2021)
Astaxanthin has antioxidant activity ten times greater than carotenoids such as -carotene and a hundred times higher than vitamin E. However, its utilization is still limited because its solubility in water is very low which results in low absorption by the skin, resulting in low bioavailability. In this case, to increase the potency of astaxanthin, this research was aimed at the formulation and characterization of astaxanthin nanoemulsions using polysorbate 80 and polyethyleneglycol 400 as a mixture of surfactants with a ratio of 7:1; 8:1 and 9:1 with the method of making a combination of low and high energy emulsification. The data obtained were analyzed using the Kruskal-Wallis test for data on the pH of the preparation and the efficiency of adsorption while the pH test during freeze-thaw stability was analyzed by the Wiloxon test. Based on the test results, it was found that the nanoemulsion preparation with the smix 9:1 formula is the most optimum formula among other formulas, which is to produce preparations with quite good characteristics organoleptically and give a light orange color appearance, clear, distinctive smell with a pH value that meets the SNI standard 16-164399-1996 with pH values ranging from 7.13 to 7.15 and based on the centrifugation test gave stable results and had particle size, polydispersity index and zeta potential values, respectively, 22.9 ± 9.4 nm, 0.435 and -21. ,4 mV and the value of entrapment efficiency ranges from 93.87% to 94.32%. However, the thermodynamic stability is not good enough. This is indicated by the instability of the preparation during the freeze-thaw test with the results of changes in color, transparency and changes in pH.Keywords: Nanoemulsion, Astaxanthin, Polyethyleneglycol 400, Polysorbate 80, Surfactants